Development of a Cell-Based Hepatitis C Virus Infection Fluorescent Resonance Energy Transfer Assay for High-Throughput Antiviral Compound Screening - Yu, Xuemei (American Society for Microbiology (ASM), 2009)
A major obstacle in the treatment of chronic hepatitis C virus (HCV) infection has been the lack of effective, well-tolerated therapeutics. Notably, the recent development of the HCV cell culture infection system now allows not only for the study of the entire viral life cycle, but also for the screening of inhibitors against all aspects of HCV infection. However, in order to screen libraries of potential antiviral compounds, it is necessary to develop a highly reproducible, accurate assay for HCV infection adaptable for high-throughput screening (HTS) automation. Using an internally quenched 5-FAM/QXL 520 fluorescence resonance energy transfer (FRET) substrate containing the HCV NS3 peptide cleavage sequence, we report the development of a simple, mix-and-measure, homogenous, cell-based HCV infection assay amendable for HTS. This assay makes use of synchronized, nondividing human hepatoma-derived Huh7 cells, which support more-reproducible long-term HCV infection and can be readily scaled down to a 96-well-plate format. We demonstrate that this stable cell culture method eliminates common problems associated with standard cell-based HTS, such as cell culture variability, poor reproducibility, and low signal intensity. Importantly, this HCV FRET assay not only can identify inhibitors that act throughout the viral life cycle as effectively as more-standard HCV assays, such as real-time quantitative PCR and Western blot analysis, but also exhibits a high degree of accuracy with limited signal variation (i.e., Z′ ≥ 0.6), providing the basis for a robust HTS campaign for screening compound libraries and identifying novel HCV antivirals.